Young adults’ risk profiles and predictive factors of Problematic Social Media Use (PSMU): a cross-sectional study - Hylkilä, Krista; Kääriäinen, Maria; Peltonen, Aino; Castrén, Sari; Mustonen, Terhi; Konttila, Jenni; Männikkö, Niko (Springer Nature, 2026)
Problematic social media use (PSMU) is a current public health concern. The current study aimed to identify the risk profiles and predictive factors of PSMU among young Finnish adults using a cross-sectional design. Survey data were analysed with K-means clustering and logistic regression, revealing three profiles: high-risk (HRG), moderate-risk (MRG), and low-risk (LRG) groups. The HRG was characterized by low conscientiousness and self-esteem, high neuroticism, and ADHD symptoms. No significant differences were noted in social support and other personality traits across profiles. Significant associations were found between profiles and sociodemographic factors, social media use duration, and motivations for use. These findings underscore the need to consider sociodemographic, psychosocial, and motivational factors in identifying individuals at risk for PSMU. The study’s outcomes can help develop effective policies and interventions for preventing and identifying PSMU.